An Ex-Post Analysis of Ginger (Zingiber officinalis) Research and Extension Investment in Bangladesh - Hasan, Md. Kamrul; Islam, M. Serajul (The Agriculturists, 2015)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> The study estimated the benefit and rate of returns to investment on ginger research and extension in Bangladesh. The Economic Surplus Model with ex-post analysis was used to determine the returns to investment and their distribution between production and consumption. Several discounting techniques were also used to assess the efficiency of ginger research. The adoption rate was found increasing over the period. The yield of modern varieties of ginger developed by Bangladesh Agricultural Research Institute (BARI) was 78 per cent higher than that of the local varieties. Society got net benefit of Tk. 432.31 million by investing in ginger research and extension. The net present value (NPV) and present value of research cost (PVRC) were estimated to be Tk. 135.01 and 81.15 million, respectively. The internal rate of return (IRR) and benefit cost ratio (BCR) were estimated to be 32 per cent and 3.75, respectively indicating that investment on ginger research and development was profitable. Ginger seed production programme should be taken largely to increase production by increasing improved variety adoption area. <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The Agriculturists <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">2014; 12(2) 103-115 <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>